Determinant factor influencing job satisfaction - Siti Roqaayah Razalli
Employees are assets that every organization needs to take precedence. Organizations that only emphasize output without regard to contributors to outputs which is employees will not be able to maintain the loyalty and diligence of employees in carrying out their duties. However, employee satisfaction will encourage the worker to produce satisfactory work and be able to enhance the organization image. Job satisfaction can be nurtured through organizational concerns over the needs of every employee. Among the needs that workers demand is from aspects of fair attention from employers, pay and promotion, providing a conducive working environment and providing a workload that is commensurate with workers responsibilities. This study was conducted among the sample of 265 support staff in Universiti Sultan Zainal Abidin which taken randomly from 48 departments and office in UniSZA Gong Badak. This study aims to look forward to job satisfaction among UniSZA support staff due to the main factor which is fairness, pay and promotion, work environment and workload. Questions for the survey to be provided to the respondents are produced by referring to the previous questionnaire. Frequency distribution and correlation variable are applied as a tool of analysis the respondent data which can give the accurate result. The results of the study showed that a positive significant relationship among job satisfaction and all the factors. This study also aims to be guidelines for solving a problem-related to job satisfaction among supporting staff and serve as a baseline for another researcher to conduct the research on the same topic but in different group focus.